Sensitivity of a Bacteroides melaninogenicus strain to monosaccharides: effect on enzyme induction. - Lev, M (1975)
The inhibition of growth in Bacteroides melaninogenicus by sugars in described. Monosaccharides such as D-glucose, D-galactose, D-mannose, and D-fructose are inhibitory at low concentrations, whereas the disaccharides sucrose and lactose are not inhibitory even at high concentrations. The major inhibitory effect of the sugar is found during the transition of lag to logarithmic growth phases. There was no primary effect of D-glucose on protein, ribonucleic acid, or deoxyribonucleic acid synthesis on cells in transition from lag to logarithmic growth. However, the addition of glucose or galactose completely abolished the induction of 3-ketodihydrosphingosine synthetase by vitamin K in vitamin K-depleted cells. Futhermore, in cells which were not vitamin K depleted, the level of this enzyme was drastically reduced by the addition of the sugar. Cyclic adenosine 5-monophosphate was unable to reverse the growth inhibition produced by glucose. In actively growing cultures, addition of sugar slows the growth rate. In these experiments the level of 3-ketodihydrosphingosine synthetase fell only after the cells had assumed the slower rate of growth. There were two indications that D-galactose was more inhibitory than D-glucose; in the presence of 0.1% D-galactose cells in lag phase did not show the increase in turbidity found in similar cells placed in medium with 0.1% D-glucose, and also D-galactose caused a greater decrease in the growth rate of actively growing cultures than was found with D-glucose. These studies suggest that the inhibitory effect of monosaccharides in lag leads to logarithmic growth transition can be ascribed to an effect on enzyme induction. On the other hand, the ability of many monosaccharides to inhibit growth, and the greater inhibitory property of D-galactose compared with D-glucose, suggests that other mechanisms may be operative as well.